2008
DOI: 10.2753/mis0742-1222250303
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Electronic Government Success: An Empirical Study

Abstract: Electronic government is being increasingly recognized as a means for transforming public governance. Despite this increasing interest, information systems (IS) literature is mostly silent on what really contributes to the success of e-government 100 TEO, SRIVASTAVA, AND JIANG Web sites. To fill this gap, this study examines the role of trust in e-government success using the updated DeLone and McLean IS success model as the theoretical framework. The model is tested via a survey of 214 Singapore e-government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
821
10
30

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,035 publications
(896 citation statements)
references
References 63 publications
35
821
10
30
Order By: Relevance
“…For example, Lee and Lin (2005) found that website design plays a major role in customer satisfaction. Teo, Srivastava and Jiang (2008) and Xiaoni and Prybutok's (2005) results show that better system quality and better service quality are related to increased user satisfaction. Yoo and Douth (2001) found that the ease of usage dimension is one of the most significant dimensions that influence customer satisfaction.…”
Section: Benefit -Satisfaction Hypothesised Relationshipmentioning
confidence: 99%
“…For example, Lee and Lin (2005) found that website design plays a major role in customer satisfaction. Teo, Srivastava and Jiang (2008) and Xiaoni and Prybutok's (2005) results show that better system quality and better service quality are related to increased user satisfaction. Yoo and Douth (2001) found that the ease of usage dimension is one of the most significant dimensions that influence customer satisfaction.…”
Section: Benefit -Satisfaction Hypothesised Relationshipmentioning
confidence: 99%
“…For example, an e-government initiative can impact individuals (e.g. Teo et al 2008, Srivastava and), nations (e.g. Srivastava and Teo 2008), corporates (e.g.…”
Section: Specify the Level Of Analysis For The Impactmentioning
confidence: 99%
“…Five studies [20,24,29,52,58] used TAM and TPB together, four of them [6,24,48,77] used even three theories or models, whereas three [32,68,74] Survey: [6], [8], [9], [12], [16], [20], [24], [29], [32], [48], [49], [52], [58], [63], [67], [68], [74], [77], [76], [79], [86]; Interview: [84], [86], [89]; Secondary Data Analysis: [31]; Case Study: [69] Information System Success Model (DeLone and McLean, 1992McLean, , 2003 Survey: [19], [22], [30], [32], [55], [59], [65], [68], [74], …”
Section: Resultsmentioning
confidence: 99%